Hypercalcaemia in rheumatoid arthritis: investigation of its causes and implications. Issue 5 (October 1979) - Kennedy, A C; Allam, R F; Rooney, P J; Watson, M E; Fairney, A; Buchanan, K D; Hillyard, C J
Abstract : When correction was made for hypoalbuminaemia, 23 of 50 ambulant patients with definite or classical rheumatoid arthritis were found to have hypercalcaemia. When these 23 patients were studied 6 months later, 7 had hypercalcaemia as defined by the correction factor for a low serum albumin level, and 6 of these patients had raised serum ionised calcium concentrations. Biochemical studies in the 23 patients indicated evidence of hyperparathyroidism, namely, hypophosphataemia, increased serum alkaline phosphatase, hyperchloraemia, and reduced tubular reabsorption of calcium. However, serum immunoreactive parathyroid hormone concentrations were normal. Only one patient had an abnormally low serum 25-hydroxy-vitamin D result: this patient had a high level of urinary D-glucaric acid and was receiving phenobarbitone for treatment of epilepsy. The biochemical features suggestive of parathyroid overactivity were particularly found in patients with raised serum calcium levels. The cause of hypercalcaemia in rheumatoid arthritis remains to be explained.